Estado Nutricional y su relación con el Desarrollo Infantil en Niños y Niñas de 0 a 3 años del Centro Infantil Municipal Centro Comercial Loja periodo Septiembre 2018-Abril 2019 - Cevallos Sánchez, Farha Carolina (2020)
The nutritional status of the child is the balance between the availability of food and the daily consumption of both nutrients and energy and the expenditure given by nutritional requirements, the imbalance of a diet can cause a poor nutritional status and according to the degree of intensity and duration affects the growth and psychomotor development of children during their early childhood. That is why the research was carried out, Nutritional status and its relationship with child development in children from 0 to 3 years of the Municipal Children's Center "CENTRO COMERCIAL LOJA", period September 2018 - April 2019. The general objective was: Determine the Nutritional Status and its relationship with Child Development in children from 0 to 3 of the Municipal Children's Center "CENTRO COMERCIAL LOJA" period September 2018-April 2019, through a quantitative, descriptive, correlational and cross-sectional study, in which the 111 boys and girls who attend the aforementioned Children's Center participated. Anthropometric measurements (weight / height) and the application of the Denver Test were taken to all the boys and girls under study. The main results of the research were: 1) Most of the boys and girls have a normal body mass index in terms of nutritional status, 2) the degree of psychomotor development that boys and girls have is normal; and, 3) regarding the relationship between the nutritional status and the psychomotor development of children, it is positive since a child with a normal nutritional status has normal psychomotor development. It was concluded that nutritional status is related to psychomotor development since as the child is better fed or has a correct weight for his age, he will obtain better psychomotor development. Keywords: Child nutrition, body mass index, psychomotor development.